NILAI MIKROBIOLOGIS DAN OKSIDASI LEMAK SOSIS DARAH (TA’BU) YANG DIBERI TAMBAHAN PASTA ASAM (Tamarindus indica) (Microbiological and lipid oxidation value of blood sausage (ta'bu) which is additional with acid paste (tamarindus indica) - Natalina E.E Gomes; Gemini E.M. Malelak; Heri Armadianto; Gustaf Oematan (Universitas Nusa Cendana, 2022)
Ta'bu is a typical food in the Sabu Island area, which is made from blood and mixed with spices and then put into the large belly of the goat, then boiled. There are no studies that report on the quality of ta, ma'am. The objective of the study was to determine the microbiological quality and lipid oxidation value in traditional blood sausage (ta'bu) which was added tamarind paste. This study used a completely randomized design (CRD) 4 x 3 , where the 4 treatments consisted of P0 = without acid paste (kontrol); P1= 2% acid paste; P2= 4% acid paste; P3 = 6% acid paste.The parameters measured were: TPC (Total Plate Count) value, Staphylococcus aureus , Salmonella sp and lipid oxidation value. The data were analyzed using SPSS 21 ANOVA. The results showed that the addition of acid paste to ta’bu reduced the TPC numbers and lipid oxidation value (P<0.05), Staphylococus aureus was the same for all treatments and Salmonella sp was negative for all treatment. The results of this study concluded that adding tamarind paste in processing ta’bu can be used to reduce the value of TPC and lipid oxidation.